Village Government Business Management (Study On Bumdes In Susukan Subdistrict, Sumbang District, Banyumas Regency) - Suryoto Suryoto; Paulus Israwan Setyoko; Denok Kurniasih Kurniasih; Ranjani Ranjani Ranjani (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2022)
Government business management is a reflection of the application of the new public management paradigm with the aim of improving the economy, and achieving efficiency and effectiveness. The purpose of this study is to analyze and describe the implementation of business principles in the management of BUMDes to improve PADes and the village economy. The research method used is descriptive qualitative research method, with data collection methods through in-depth interviews, observation and documentation. Meanwhile, the data analysis method was carried out using an interactive analysis model. The results of the study indicate that business planning in managing BUMDes can still be made in a simple format and does not involve the participation of local villagers. Even though it is made simply, the Susukan BUMDes continues to run with the encouragement and commitment of the Susukan Village Head. As an effort to motivate BUMDes management, it is carried out through a payroll system. The Village Head is directly involved in the process of implementing his business, starting from the preparation of plans, socialization, to the implementation of control over the business being run and reporting. In addition, the Susukan Village Head also established various collaborations with various stakeholders as a form of encouragement to the BUMDes management.